Entrepreneurial competencies of undergraduate students: The case of universities in Nigeria. Issue 1 (March 2021) - Okolie, Ugochukwu Chinonso; Igwe, Paul Agu; Ayoola, Amos Aderemi; Nwosu, Hyginus Emeka; Kanu, Clementina; Mong, Ifeanyi Kalu
Abstract: The present study builds on Morris et al.'s entrepreneurial competencies (ECs) identified from their 2013 Delphi study, to examine whether students' compulsory participation in entrepreneurship education (EE) in Nigerian higher education institutions (HEIs) influences their development of the identified 13 ECs for business start-up after graduation. Data were collected from 1191 final year undergraduates in 12 public universities within the six geo-political zones of Nigeria using questionnaire derived from the constructs of the 13 identified ECs. Findings show that students' participation in EE associated positively with five of the thirteen ECs including opportunity recognition, opportunity assessment, creative problem-solving, self-efficacy and building and using networks. However, we found no evidence of a positive association between students' participation in EE and the development of the remaining eight ECs including risk management/mitigation, conveying a compelling vision, tenacity/perseverance, resource leveraging, guerrilla skills, value creation through innovation, ability to maintain focus yet adapt, and resilience. This study contributes to the body of knowledge and covers a gap in the literature about the paucity of research on whether students' compulsory participation in EE in Nigerian HEIs help to improve students' development of the identified 13 ECs for business start-up after graduation. Also, while the study focused on Nigeria, the findings apply to other countries that have similar issues addressed in this study. Highlights: We drew on Morris et al.'s (2013) identified entrepreneurial competencies from Delphi study. Entrepreneurship education influenced five of the thirteen entrepreneurial competencies. Participation in entrepreneurship education predicted opportunity recognition. The use of innovative teaching techniques can improve students' development of ECs. Entrepreneurship programs should be practical based rather than theory-based.